IMPLEMENTASI FATWA DSN-MUI NOMOR 4/DSN-MUI/2000 TENTANG MURABAHAH PADA BMT DI PROVINSI LAMPUNG - Liky Faizal; Ruslan Abdul Ghofur; juliana, juliana (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2020)
Writing this journal is motivated by the author's curiosity to find out the financing mechanism for BMT DMS and BTM BIMU in applying Murabahah financing products. More specifically, this study is aimed at analyzing the suitability of the DSN-MUI fatwa regarding Murabahah with the operational procedures for Murabahah financing at BMT DMS and BTM BIMU. In addition, the central position of DSN-MUI as the holder of authority over the status of halal products in Islamic Financial Institutions in Indonesia, LKMS is obliged to comply with all DSN-MUI fatwas regarding the financial products they practice. Murabahah financing products are financing products that are certainly profit and profitable, so they become superior products at BMT DMS and BTM BIMU. Then how is the implementation of murabahah financing at BMT DMS and BTM BiMu and how is the fatwa analysis of DSN MUI No. 04 / DSN-MUI / IV / 2000 on murabahah financing at BTM BiMu and BMT DMS. With the aim of this thesis research is Knowing the implementation of murabahah financing in BTM BiMu and BMT DMS and Knowing the DSN-MUI fatwa analysis on murabahah financing on BTM BiMu and BMT DMS. Data processing methods from research used, namely by interview, observation and literature study methods or with primary data and secondary data. This research is a field research, and the method used is descriptive qualitative analysis. In addition, the analysis also uses inductive analysis. The results show that the implementation of Murabahah in BTM BiMu and BMT DMS generally uses two models, namely direct Murabahah and represented murabahah (bil wakalah). In general, the practice of direct murabahah financing has met the requirements imposed by the DSN-MUI.